Comparative analysis of contemporary anti-double stranded DNA antibody assays for systemic lupus erythematosus - Bauer, Claus-Juergen; Karakostas, Pantelis; Weber, Nadine; Behning, Charlotte; Stoffel-Wagner, Birgit; Brossart, Peter; Dolscheid-Pommerich, Ramona; Schäfer, Valentin Sebastian (Frontiers in Immunology, 2023)
Objective: Elevated double-stranded DNA (dsDNA) antibody levels in blood serum are considered a disease-specific marker in systemic lupus erythematosus (SLE), correlate with disease activity and the incidence of lupus nephritis, and can be detected in up to 86% of all SLE cases. Despite the high clinical relevance, the variety of dsDNA antibody testing methods with heterogenous performance in clinical use remains challenging. This study is the first to prospectively investigate the performance of two of today's most commonly applied anti-dsDNA testing methods head-to-head under real-world conditions, as well as their correlation with other clinical and serological disease parameters in SLE patients.Methods: In this prospective study, all SLE patients undergoing treatment at the Department of Rheumatology at the University Hospital Bonn within a 13-months period (n=41) and control patients without connective-tissue disease (n=51) were consecutively enrolled and examined. For all study participants' serum samples both anti-dsDNA-NcX enzyme-linked immunoassay testing (EURO-IMMUN, Luebeck, Germany) and the fluorescence immunoassay ELiA dsDNA (Thermo Fisher Scientific, Waltham, USA) were performed. In addition, demographic data, further laboratory values and disease activity parameters were recorded. Clinical disease activity was assessed by SLEDAI-2K.Results: Both assays showed high specificity (anti-dsDNA-NcX ELISA: 0.9, ELiA dsDNA: 0.959), but there were notable differences in sensitivity (anti-dsDNA-NcX ELISA: 0.51, ELiA dsDNA: 0.38).Pearsons's correlation yielded a positive correlation between anti-dsDNA concentrations and CRP concentrations for the anti-dsDNA-NcX ELISA (R=0.22; p=0.038) and a mild-to-moderate inverse correlation between concentrations of anti-dsDNA and complement C4 for the ELiA dsDNA test (R=-0.22; p=0.045) when SLE and control patients were considered together. Other than that, no significant correlation between anti-dsDNA concentrations and clinical or laboratory findings was found for either test procedure.Conclusion: Both anti-dsDNA antibody assays represent reliable examination methods with high specificity for the diagnosis of SLE that fulfill EULAR/ACR requirements. However, the anti-dsDNA-NcX ELISA showed superior sensitivity and significant correlation with disease activity (as measured by CRP concentrations).